RAG-1 and RAG-2, Adjacent Genes That Synergistically Activate V(D)J Recombination - Oettinger, Marjorie A.; Schatz, David G.; Gorka, Carolyn; Baltimore, David (Science (American Association for the Advancement of Science), 1990)
The vast repertoire of immunoglobulins and T cell receptors is generated, in part, by V(D)J recombination, a series of genomic rearrangements that occur specifically in developing lymphocytes. The recombination activating gene, RAG-1, which is a gene expressed exclusively in maturing lymphoid cells, was previously isolated. RAG-1 inefficiently induced V(D)J recombinase activity when transfected into fibroblasts, but cotransfection with an adjacent gene, RAG-2, has resulted in at least a 1000-fold increase in the frequency of recombination. The 2.1-kilobase RAG-2 complementary DNA encodes a putative protein of 527 amino acids whose sequence is unrelated to that of RAG-1. Like RAG-1, RAG-2 is conserved between species that carry out V(D)J recombination, and its expression pattern correlates precisely with that of V(D)J recombinase activity. In addition to being located just 8 kilobases apart, these convergently transcribed genes are unusual in that most, if not all, of their coding and 3′ untranslated sequences are contained in single exons. RAG-1 and RAG-2 might activate the expression of the V(D)J recombinase but, more likely, they directly participate in the recombination reaction.